<h3>Answer: Check out the screenshots below.</h3>
=========================================
Explanations:
Part 1
For the first box, we use the log rule that log(A)+log(B) = log(A*B)
Then in the second box, we'll convert to exponential form. The logs are assumed to be base 10.
The third box then factors and uses the zero product property.
----------------------------
Part 2
We check each solution generated in part 1.
Plugging x = 5/3 will lead to the same number on each side. Therefore, x = 5/3 is a true solution.
In contrast, plugging x = -2 leads to a false equation. Recall that the domain of y = log(x) is x > 0. This means we cannot replace x with negative numbers. The value x = -2 is extraneous.
----------------------------
Part 3
There's not much to explain here that isn't already done so on the screenshot below.
9514 1404 393
Answer:
all are Not Equivalent
Step-by-step explanation:
The coefficient of t³ in the target expression is -3. In order for that to be the result of simplifying any of the given expressions, they must have ( )^(t^3) in the denominator. None do, so none of the offered choices is equivalent to the given expression.
_____
The expressions simplify like this:
Answer:
x = 21
Step-by-step explanation:
Givens:
Every triangle's interior angles add up to 180°
The triangle has a right angle.
The triangle is isosceles (two equal sides and two equal angles)
Let's make an equation with the information we have already.
2 × (2x + 3) + 90 = 180
4x + 6 + 90 = 180
4x + 96 = 180
4x = 84
x = 21
The correct sequence of events in protein synthesis is transcription, then translation.
Answer:
y+2 = -3(x-2)
Step-by-step explanation:
Point slope form of an equation is
y-y1 = m(x-x1) where m is the slope and (x1,y1) is a point on the line
y - -2 = -3( x-2)
y+2 = -3(x-2)